2012
DOI: 10.5606/tgkdc.dergisi.2012.110
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of cilostazol and levosimendan on lung injury induced by lower limb ischemia-reperfusion

Abstract: Amaç: Bu çalışmada, abdominal aort cerrahisinde iskemi/ reperfüzyon (İ/R) sonrası uzak organ hasarı olarak akciğer üzerine silostazol, levosimendan ve bu ilaçların kombinasyonunun etkileri araştırıldı.Ça lış ma pla nı: Çalışma ortalama 219±26 g ağırlığında 35 erkek Wistar albino türü sıçan ile gerçekleştirildi. Sıçanlar her bir grupta yedi sıçan olacak şekilde randomize olarak beş gruba ayrıldı. Sıçanlara silostazol, levosimendan ve bu iki ilacın kombinasyonu ile tedavi uygulandıktan sonra, infrarenal aortik o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 22 publications
3
11
0
Order By: Relevance
“…These findings are in agreement with earlier studies on lung injury induced by lower limb I/R [57] and spinal cord I/R-induced injury [58]. These reports support the possible antioxidant capacity of cilostazol, which could be one of its renoprotective mechanistic pathways.…”
Section: Discussionsupporting
confidence: 93%
“…These findings are in agreement with earlier studies on lung injury induced by lower limb I/R [57] and spinal cord I/R-induced injury [58]. These reports support the possible antioxidant capacity of cilostazol, which could be one of its renoprotective mechanistic pathways.…”
Section: Discussionsupporting
confidence: 93%
“…Lipid peroxidation seen in diabetic patients further increases the damage to distant organs following reperfusion of the myocardium exposed to ischaemia ( 4 ). Among the distant organs, indirect damage seen after I/R is defined best in the lung ( 5 ) and is associated with these mechanisms. Therefore, acute lung injury may indirectly develop during and after pulmonary oedema.…”
mentioning
confidence: 99%
“…They showed cilostazol and diltiazem were effective to decrease renal I/R injury. In another experimental study investigating the protective effects of cilostazol and levosimendan on lung injury after lower extremity ischemia, Onem et al [16] performed 60 min abdominal aortic crossclamping and evaluated malondialdehyde levels, superoxide dismutase activity, and glutathione levels in the lung tissues. The authors showed that cilostazol and levosimendan restored malondialdehyde levels, superoxide dismutase activity, glutathione levels, and lung injury scores.…”
Section: Discussionmentioning
confidence: 99%